Let's heat it - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Following the lead of other Pacific islands, the Samoan government has procured a High Temperature Forced Air facility (HTFA) to comply with import and pest quarantine regulations in New Zealand and Australia (see also Spore 92). The Samoan...